PENGARUH BEBAN KERJA TERHADAP STRES KERJA GURU HONORER SEKOLAH MENENGAH PERTAMA NEGERI KOTA CIMAHI - Nida Alya Luqiana, - (2022)
This research is entitled "Influence Of Workload On The Work Stress Of Honorary Teachers of Cimahi City State Junior High School". In general, this study aims to find out and obtain an overview of the effect of workload on work stress on honorary teachers at Cimahi City State Junior High School. The method used in this study is a descriptive method with a quantitative approach. The data collection technique used a closed questionnaire on 57 respondents by proportional stratified random sampling. With the help of Microsoft Excel 2013 and SPSS version 26.0 for Windows. Based on the results of the Weight Means Score calculation, the general description of the X variable is in the very high category and the Y variable is in the medium category. Furthermore, based on the results of the correlation test between variables X and Y, the value is -0,202. For the determination test, it was found that the X variable had an effect of 4.1% on the Y variable. While the results of the significance test obtained the value of tcalculation is -1.529 while ttable was 1.67303, then tcalculation<ttable, and there was no significant effect between the X and Y variables. The results of the regression analysis obtained the equation = 60,092+(-0,202)X. The conclusion of this study states that workload does not have a significant effect on the work stress of honorary teachers, and there are other factors that were not studied in this study that can cause work stress.